Cytologic features of cutaneous follicular tumors and cysts in dogs. (1st March 2017) - Adedeji, Adeyemi O.; Affolter, Verena K.; Christopher, Mary M.
Abstract : Background: Follicular tumors and cysts are common skin lesions in dogs. Both are distinguished based on their cellular origin (matrical, isthmus, or infundibular cells) and the type of keratin they produce. Typically, differentiation requires histopathology, as all these lesions often have similar cytologic features. Objectives: The goal of this retrospective study was to identify unique cytologic features that may assist differentiation of canine benign follicular tumors and cysts at cytology, using histopathology as gold standard. Methods: Electronic medical records of the University of California–Davis Veterinary Medical Teaching Hospital were searched for diagnoses of follicular tumors and cysts in dogs that had both histopathologic and cytologic diagnoses between January 2000 and December 2013. Cytologic specimens were reassessed in a blinded manner for the presence and type of background, cells, noncellular elements, and inflammation. Results: Forty‐six samples were included in the study. Follicular cysts ( n = 25) and infundibular keratinizing acanthomas ( n = 5) contained sheets of keratinized anucleate to nucleated squamous cells. Trichoepitheliomas ( n = 8) had 2 primary cytologic presentations: those with primarily basaloid cells that appeared to be undergoing keratinization (3/8; 38%) and those with keratinizing anucleate to nucleated squamous cells (5/8; 63%). Trichoblastomas ( n = 8) had pink matrix with spindle cells and contained cohesive clusters of basaloid cells. Conclusion: Trichoblastomas, and to a lesser extent, trichoepitheliomas, have unique cytologic features with the potential to distinguish them from other benign follicular tumors and cysts. These results are an important first step toward improving the diagnostic specificity of cytologic examination of cutaneous follicular lesions.